11. KONFLIK SOSIAL : SUATU TINJAUAN TEORITIS SOSIOLOGIS - Hidayah, Zainal (FORUM, 2008)
Social dis-integration is still a latent problem faced by the Indonesians up to the present time. As a big archipelago country with more than 230 million inhabitants scattered in thousands of islands, the intensity of social conflict always present and there is a tendency to increase. This article describes about social conflict based on sociological theoritical perspective. Basic factors which can arise social conflict are pluralities in religion and ethnic, disharmonious relationship between the majority and the minority, disparity between the poor and the rich, disparity between centre and periphery, as well as disparity between periphery and periphery. But actually all of these factors are based on unequality in the distribution of life resources and social position.